2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23358
|View full text |Cite
|
Sign up to set email alerts
|

A Blocks-based Visual Environment to Teach Robot-Programming to K-12 Students

Abstract: was selected for a three-year term as a Senior Faculty Fellow of NYU-SoE's Othmer Institute for Interdisciplinary Studies. His scholarly activities have included 3 edited books, 7 chapters in edited books, 1 book review, 55 journal articles, and 109 conference papers. He has mentored 1 B.S., 16 M.S., and 4 Ph.D. thesis students; 31 undergraduate research students and 11 undergraduate senior design project teams; over 300 K-12 teachers and 100 high school student researchers; and 18 undergraduate GK-12 Fellows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…It is also indicated that these robot systems (PIC microcontroller, Arduino or Raspberry Pi based and programmed by Blockly), which do not require the installation of any additional software, can be used successfully even for 3 rd and 4 th grades. A Robot, developed by Yadagiri et al (2015) to teach basic concepts of programming by robot programming, a labyrinth based instructional game and results of another study in which block based visual robot programming tool was used, showed that use of such learning environments in programming education for 12 th grades facilitated fast, simple and entertaining learning.…”
Section: Introductionmentioning
confidence: 99%
“…It is also indicated that these robot systems (PIC microcontroller, Arduino or Raspberry Pi based and programmed by Blockly), which do not require the installation of any additional software, can be used successfully even for 3 rd and 4 th grades. A Robot, developed by Yadagiri et al (2015) to teach basic concepts of programming by robot programming, a labyrinth based instructional game and results of another study in which block based visual robot programming tool was used, showed that use of such learning environments in programming education for 12 th grades facilitated fast, simple and entertaining learning.…”
Section: Introductionmentioning
confidence: 99%
“…The app allows the students to program an Arduino-compatible development board using the Bluetooth protocol through graphical blocks as Figure 3 shows. The blocks were created using the Google tool Blockly, which is a web engine tool that has been widely employed to teach programming languages from school to university levels and it acts as a parser and translator for the graphical blocks toward the selected programming language [22,68,80]. Using the blocks, the students can construct algorithms and interact with elements interfaced with the development board such as LCD, IoT devices, sensors, or robots.…”
Section: Softwarementioning
confidence: 99%
“…Outros trabalhos que serão apresentados nesse capítulo foram obtidos na Revisão Inicial da Literatura. Os trabalhos de [Krishnamoorthy and Kapila 2016] e [Miller et al 2018] estão inteiramente relacionados a atividades desplugadas, enquanto que os trabalhos de [Bravo et al 2017], [Baião et al 2017], [Goud Yadagiri et al 2017], [Sales et al 2017] e [Queiroz et al 2017] estão mais relacionados à linguagens visuais e Robótica educacional. A Tabela 1 apresenta um resumo comparativo dos principais trabalhos correlatos a este.…”
Section: Trabalhos Relacionadosunclassified